Supramolecular Assembly of TPE‐Based Glycoclusters with Dicyanomethylene‐4H‐pyran (DM) Fluorescent Probes Improve Their Properties for Peroxynitrite Sensing and Cell Imaging - Dong, Lei; Fu, Mengqi; Liu, Lifang; Han, Hai‐Hao; Zang, Yi; Chen, Guo‐Rong; Li, Jia; He, Xiao‐Peng; Vidal, Sébastien (Chemistry : a European journal, 2020)
Two red‐emitting dicyanomethylene‐4H‐pyran (DM) based fluorescent probes were designed and used for peroxynitrite (ONOO−) detection. Nevertheless, the aggregation‐caused quenching effect diminished the fluorescence and restricted their further applications. To overcome this problem, tetraphenylethylene (TPE) based glycoclusters were used to self‐assemble with these DM probes to obtain supramolecular water‐soluble glyco‐dots. This self‐assembly strategy enhanced the fluorescence intensity, leading to an enhanced selectivity and activity of the resulting glyco‐dot comparing to DM probes alone in PBS buffer. The glyco‐dots also exhibited better results during fluorescence sensing of intracellular ONOO− than the probes alone, thereby offering scope for the development of other similar supramolecular glyco‐systems for chemical biological studies. Self‐assembly of TPE‐based glycoclusters with fluorogenic probes allowed for the detection of peroxynitrite in vitro and in cell assays through the recovery of proper water solubility and fluorescence emission.